2011
DOI: 10.5137/1019-5149.jtn.5422-11.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prenatal stress on expression of glutathione system in neonatal rat brain

Abstract: AIm: Prenatal stress is known to adversely affect the fetal brain development and also neuronal loss. The mechanism(s) associated with prenatal stress induced developmental neurotoxicity remains obscure. Few studies point to the glutathione (GSH) antioxidant system which is an important molecular target for this toxicant. Hence the present study investigates the effect of prenatal stress on glutathione system in neonatal rat brain. mATeRIAL and meTHods: Three to four months old pregnant Wistar rats were subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
(21 reference statements)
3
6
0
Order By: Relevance
“…As per our earlier study, resveratrol has a direct effect on fetal brain during gestation by protecting the antioxidant defense in growing brain (Sahu et al, 2012). Hence we believe that resveratrol crossed the placental barrier and exerted a direct effect on growing brain in rat pups.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…As per our earlier study, resveratrol has a direct effect on fetal brain during gestation by protecting the antioxidant defense in growing brain (Sahu et al, 2012). Hence we believe that resveratrol crossed the placental barrier and exerted a direct effect on growing brain in rat pups.…”
Section: Discussionsupporting
confidence: 73%
“…A number of studies suggest that prenatal stress is associated with alterations in the offspring HPA axis activity. In our previous study we confirmed that prenatal stress is associated with higher basal glucocorticoid (GC) secretion in the off spring (Sahu et al, 2012). A large body of evidence has been gathered, demonstrating that elevated levels of glucocorticoids, affects both hippocampal structure and function (McEwen, 2008), as the hippocampus is densely populated with receptors for GC hormones, stress and glucocorticoids strongly inhibit adult neurogenesis, leads to cognitive impairments and depressive illness.…”
Section: Discussionsupporting
confidence: 64%
“…It has previously been shown that oxidative damage produced by prenatal restrain stress resulted in neuronal loss in rat offspring [22C]. Exposure to early as well as late gestational stress brought about brain oxidative damage where decline in SOD, GSH and GSSG-Rd activities [23,39], increase in lipid peroxidation and decrease in total antioxidant capacity were observed [22]. An increase in the content of reactive oxygen species in the hippocampus of prenatally stressed rat offspring was reported by Li et al [20].…”
Section: Discussionmentioning
confidence: 99%
“…An elevation in MPO activity was observed after etoposide treatment, which indicates the acculamation of neutrophils that might contribute to etoposide induced small intestinal damage. 36 The levels of MPO in current study is significantly increased in rats that received etoposide alone when compared to normal control may be due to increased levels of free radicals generated during the development of mucositis. There was significant decrease in the level of MPO in the rats which received etoposide followed by Spondias pinnata, whey preparation and the combination.…”
Section: Discussionmentioning
confidence: 78%